Hidroponik dengan Konsep Agro Voltec Guna Optimalisasi Kemandirian dan Ketahanan Pangan di Kelurahan Rejowinangun Selatan Kota Magelang - Alifia Revan Prananda; Cornelius Rangga Surya Kusuma; Daniel Gunawan; Terra Rhebekka; Galih Slamet (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
Increasing population density and concretization in urban areas, such as Magelang City, have caused a significant decrease in green open spaces (RTH), which has an impact on food security and independence. Magelang City, with a population density of 7,361 people/km², faces a major challenge in providing adequate green spaces to support local food production. Rejowinangun Selatan Village, as one example, shows the limited green open spaces available. To overcome this problem, urban farming, especially through hydroponic techniques, offers an effective solution. The methods applied in this community service include various approaches to educate and directly involve the community in the practice of making hydroponics with solar panels. By utilizing renewable energy-based technology, such as solar panels and integrated electrical systems, hydroponic farming allows food production in limited spaces such as house terraces. This system not only increases food independence and security, but also ensures that the vegetables produced are healthier because of the minimal use of pesticides. Urban farming with the hydroponic method can optimize the use of limited space and become a productive and sustainable alternative for urban communities.